Variabilitas, Heritabilitas, dan Hasil Padi Gogo F3 Persilangan Kultivar Lokal Aceh x Ciherang - Yenni Marnita; Ainul Mardiyah; Muhammad Syahril (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2021)
The increase in the area of land affected by drought due to climate change requires breeders to develop rice varieties adaptive to drought. The purpose of this research was to study the heritability of F3 populations derived from the crossing between local rice variety Sileso (high yielding and drought tolerant) with Ciherang rice variety (early maturing) and to select high yielding and early maturing genotype. The F3 populations, their reciprocal, and parents were used in the study. The experiment was conducted in the experimental field of the Faculty of Agriculture, Samudra University, Langsa, Aceh, from August to December 2020. High heritability on the days to harvest and yield per plant characters were only obtained in the family A1B and A2B. The populations A1B had a heritability value on yield per plant of 0.61 and days to harvest of 0.85. The populations A2B had a heritability value on yield per plant of 0.68 and days to harvest of 0.73. Results from the selection in the F3 population obtained 11 genotypes which had high yield and early maturity, namely: A3B(13), A1B(25), A1B(201), A1B(208), A1B(282), A1B(297), A1B(303), A2B(38), A2B(221), A2B(358), and A2B(424). The average yield per plant and days to harvest of these genotypes was 90.67 g and 117 days, respectively. Keywords: drought tolerant, early maturing, reciprocal